Analysis of the compressibility of edible powders under low pressure. (March 2022) - Shen, Changpu; Li, Yongxiang; Xu, Xuemeng
Abstract: Appropriate compression of edible powder is very beneficial to the powder itself and the industrial production, but the law and mechanism of the influence of various factors on the compressibility of powder are not clear. Therefore, this study was used uniaxial confined real compression experiments to separately study the influence law of particle size distribution, moisture content and static friction angle on powder compressibility. Through uniaxial confined compression real and simulation experiments, combined with powder particle size distribution experiment, powder moisture content measurement experiment, powder angle of repose experiment and powder static friction angle experiment, the internal mechanism of different factors affecting powder compressibility was analyzed. The results show that the compressed volume of powder increases logarithmically with the increase of pressure. The higher the moisture content of the powder (11%, 14%, 18%), the larger the void content, the worse the fluidity and the compression curve of high moisture content is always above that of the low moisture content (The average difference of amount of compression was 3.24%). The larger the particle size distribution range of the powder, the larger the void content, the better the fluidity and the compression curve of wheat flour is always above the wheat starch (The average difference of amount of compression was 3.08%). When using different containers, the larger the static friction angle between powder and container, the greater the static friction between powder and container (the compression resistance of the powder) and the worse the compressibility, but the effect on the compressibility is small (The compressibility gap of powder in different containers is within 0.7%.). Highlights: Study the influence of different factors on the compressibility of powder. Explore the influence mechanism of different factors on compressibility of powder. The calibration of the parameters provides a basis for the numerical simulation of the powder.